PENGEMBANGAN JARINGAN PIPA DISTRIBUSI AIR BERSIH DI KECAMATAN TAPA - Alitu , Aryati (Jurnal Entropi, 2009)
Clean Water service in Tapa District still be very low, because of clean water processing system still use the system of Tardy Sand Filter processing (SPL) where its processing building still very simple and have old, network of distribution pipe a lot leak so that requirement of water resident will be clean cannot be fullfiled better. For that needed by a complete processing development planning so that clean amount of water required in Tapa District can be fullfiled. Planning clean water processing development use the projection analysis sum up the resident with the method aritmatika. This method assumed by a accretion sum up the constant resident so that can plan the domestic clean amount of water required, non domestic, clock culminate, head loss and capacities produce the water up to year 2015. Research result indicate that the clean amount of water required reach 70 litre/second, so that existing processing system this time that is SPL represent the processing which still modestly in its processing building meaning not yet complete, so that have improper again utilized because unable to again provide the water besih of]according to resident requirement. For that need the clean water processing planning by using Processing Installation Complete with system branch network of distribution pipe to fulfill resident requirement up to year 2015 by kontinu, with quality and amount.